PTU-188 Repeat Video Capsule Endoscopy- is it Worth It?. (4th June 2013) - Parker, C; Rajasekhar, P; Bevan, R; Davison, C; Panter, S
Abstract : Introduction: Few studies have reported on the yield of repeat capsule endoscopy (CE) in the same patient; data regarding this diagnostic strategy are limited. 1, 2 The aims of this work were to assess the indications for repeat capsule and to determine the diagnostic yield of repeat capsule in our trust. Methods: A retrospective review of all patients who underwent CE at South Tyneside District Hospital between August 2004 and October 2012 was conducted. Patients who underwent a repeat CE were identified and divided into one of four subgroups. Findings were classified as positive or negative; positive findings were taken as presence on report of ulcers, tumours, strictures, polyps, blood or angioectasia. Results: A total of 1083 studies were performed, 83 were repeat studies. 7 patients were noted to have greater than 2 repeats. Indications: Group 1 Gastric retention or technical failure (N = 16) Group 2 Surveillance (N = 7) Group 3 Poor views (as commented on by reporting physician on report) or incomplete (not seen to enter the colon) on initial study (N = 31) Group 4 Ongoing symptoms/assessment of disease extent/unclear findings on initial VCE (N = 36) (7 cases are reported in both group 3 and 4) Yield: Overall yield, excluding gastric retention was 38% for the first study and 46% for 2 nd study, of those with an initial negative study (42 patients), 21% of these had a positive repeat. (those with poor views had been given bowel preparation, those with an incomplete capsule study had a capsule recording time of 8–9 hours on both studies). Positive findings Subgroup analysis group 4: - Ongoing symptoms with consistent with ?Crohn's or known Crohn's the yield remains the same on 1 st and 2 nd capsule 4/9 (44%). - Ongoing IDA/GI bleeding show an increased yield with 8/17 (47%) having a positive 1 st study and 10/17 (59%) a positive 2 nd study. 21 had a repeat despite a positive 1 st study (excluding surveillance), 71% had positive repeat with resulting change in management in 73%. 9/15 done for ongoing symptoms, 6/15 for incomplete/poor views. Conclusion: Limited data exist regarding the yield of repeat CE, it is suggested by the literature that yield of a repeat study is better in those with GI bleeding/anaemia. Our results suggest that the group with the highest yield (3 fold increase) on repeat are those with poor views or an incomplete initial study. There is an improvement in yield with 2nd study for those with ongoing symptoms of IDA or GI bleeding in keeping with previous literature. Disclosure of Interest: C. Parker Grant/Research Support from: Imotech Medical, P. Rajasekhar: None Declared, R. Bevan: None Declared, C. Davison: None Declared, S. Panter: None Declared References: Yield of repeat VCE in obscure GI bleeding. Jones et al. Am J Gastro 2005:100(5); 1058–64 Diagnostic yield of repeat capsule endoscopy. Svarta et al. Can J Gastro 2010:24(7); 441–22